An analysis of cognitive levels of English test designed by English teachers at SMAN 5 Kendari - Naoza, Naoza; Lio, Asrun; Nggawu, La Ode (Journal of Teaching of English, 2022)
This study aimed to find out the cognitive levels of English test questions designed by English teachers at SMAN 5 Kendari. In collecting the data, the researcher used documentation and interviews as the instrument. The data analysis used in this study was a qualitative data analysis method, in which the results of the study were described descriptively. The item questions analyzed were a summative test used in the midterm exam and final exam at the 10th, 11th, and 12th grade of 2021/2022academic year. The analysis used Bloom's taxonomy revised by Anderson & Krathwol (2001). The results of the study showed that among 109 questions, there were 28 (25%) questions categorized as remembering level, 60 (55%) categorized as the understanding level, 5 (5%) categorized as applying level, 14 (13%) categorized as analyzing level, 1 (1%) questions categorized as evaluating level, and 3 (3%) questions categorized as creating level. Moreover, the results have obtained the percentage of LOTS, MOTS, and HOTS of English test questions as follows; 80% of questions categorized as LOTS, 4% of questions categorized as MOTS, and 16% of questions categorized as HOTS. Therefore, it can be concluded that the English test at SMAN 5 Kendari was dominated by lower-order thinking level questions.